The I-space as an evolutionary framework for an economics of knowledge : a comparison with generalized Darwinism - Naidoo, Satiaseelan (Stellenbosch : Stellenbosch University, 2008)
Thesis (MPhil (Information Science))--Stellenbosch University, 2008.